Optimising stocking strategies in Sri Lankan reservoir culture-based fisheries: some bioeconomics and sustainability concerns - Digamadulla, D.S.; Amarasinghe, U.S.; Petersen, E.H.; Jones, C.M.; De Croos, M.D.S.T. (Australian Center of International Agricultural Research, 2026)
The sustainability of the CBF system depends on the balance between stocking and extension practices. This current study focused on selected 24 reservoirs’ CBF practices and its economics. During the study we have identified that stocking is a prerequisite, which has been the source of CBF as well as the reservoir fishery of Sri Lanka. Here, the question of interest is whether the intensification of stocking is profitable and sustainable. Descriptive and preliminary bioeconomic analysis was conducted. Primary data were sourced from the logbooks of RFOs and the National Aquaculture Development Authority databases (2019–2020), while secondary data were obtained from RFO administrative and financial records. Stakeholder perception survey on CBF sustainability was included with 176 participants to supplement data. It is evident that the stocking has been conducted arbitrarily , which is obvious in the ad hoc production. The stocking efficiency per area (SEA) has been affected by both fishing intensity (FI) and stocking density (SD) at different rates across the reservoir types. The questionnaire outcomes concluded that intent to increase stocking are with expectation of higher income. From fisher opinions, it is understandable that the economic sustainability has the higher leverage compared to the environmental sustainability
Keywords: Bioeconomics; Culture-based fishery; Reservoirs